2020
DOI: 10.1093/mnras/staa246
|View full text |Cite
|
Sign up to set email alerts
|

The paradox of youth for ALMA planet candidates

Abstract: Recent ALMA observations indicate that the majority of bright protoplanetary discs show signatures of young moderately massive planets. I show that this result is paradoxical. The planets should evolve away from their observed states by radial migration and gas accretion in about 1% of the system age. These systems should then hatch tens of giant planets in their lifetime, and there should exist a very large population of bright planet-less discs; none of this is observationally supported. An alternative scena… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 132 publications
(182 reference statements)
0
3
0
Order By: Relevance
“…One of the first images to come from ALMA was the now famous HL Tau disc, a disc surrounding a young, nearby star in the Taurus star-forming region [67]. Further observational studies, in particular, the Disc Substructures at High Angular Resolution Project (DSHARP) [68], have shown that discs around young stars display features than can be attributed to a change in disc composition [69][70][71][72] as a function of radius, or the presence of fledgling planets within those discs [73][74][75][76][77] (although the latter scenario is still hotly debated [78,79]).…”
Section: Destruction Of Protoplanetary Discsmentioning
confidence: 99%
“…One of the first images to come from ALMA was the now famous HL Tau disc, a disc surrounding a young, nearby star in the Taurus star-forming region [67]. Further observational studies, in particular, the Disc Substructures at High Angular Resolution Project (DSHARP) [68], have shown that discs around young stars display features than can be attributed to a change in disc composition [69][70][71][72] as a function of radius, or the presence of fledgling planets within those discs [73][74][75][76][77] (although the latter scenario is still hotly debated [78,79]).…”
Section: Destruction Of Protoplanetary Discsmentioning
confidence: 99%
“…One of the first images to come from ALMA was the now famous HL Tau disc, a disc surrounding a young, nearby star in the Taurus star-forming region [63]. Further observational studies, in particular the Disk Substructures at High Angular Resolution Project (DSHARP) [64], have shown that discs around young stars display features than can be attributed to a change in disc composition [65][66][67][68] as a function of radius, or the presence of fledgling planets within those discs [69][70][71][72][73] (although the latter scenario is still hotly debated [74,75]).…”
Section: Destruction Of Protoplanetary Discsmentioning
confidence: 99%
“…On the other hand, high-resolution imaging toward a targeted group of disks has shown that large and massive disks are often associated with substructures, mostly seen as gaps and rings (e.g., Partnership et al 2015;Andrews et al 2018a;Long et al 2018;Cieza et al 2021), but also as arcs and spiral arms (van der Marel et al 2013;Huang et al 2018b;Dong et al 2018). Given the ubiquitous nature of planetary systems in the Galaxy (e.g., Winn & Fabrycky 2015), the frequent appearance of disk substructures suggests that they might be relevant to the process of planet formation, though establishing the direct connection between a disk feature and a planet is so far challenging, considering the complex physics involved in disk and planet evolution (e.g., Nayakshin 2020).…”
Section: Introductionmentioning
confidence: 99%